Efficiency of Bacillus Cereus Strain ATCC 14579 in Rice Washing Water Formulation as an Inoculant Agent in Seed Corn Growth - Maimuna Nontji; Saida Saida; Suriyanti Salama; Muliaty Galib; Ida Suryani (International Journal of Halal System and Sustainability, 2022)
This study aimed to determine the efficient formulation dosage of rice washing water for Bacillus cereus Strain ATTC 14579 as inoculant agent on seed growth of corn in micro plot scale. Experiment method was used by randomized block design factorial, consisting of two factor, the first factor is variety, namely V1: Anoman variety and V2: Bima URI 19 variety, the second factor is dosage of inoculant agent in rice washing water formulation, namely D1= 20 mL inoculant agent/kg of seed,D2= 40 mL inoculant agent/ kg of seed, D3= 60 mL inoculant agent/ kg of seed, D4= 80 mL inoculant agent/kg of seed, D5= 100 mL inoculant agent/kg of seed and D6= control (without formulation dosage). Each treatment was repeated three times, so that there were 42 experimental units. The result showed that the formulation dosage of 80-100 mL inoculant agent/kg of seed was an efficient to increase the growth of seed corn verities Anoman and Bima URI 19.